Bridging the Gaps among Mixed Ability Students to Create Conducive Atmosphere in Learning English through Various Communication Activities - Aminah (International Journal in Applied Linguistics of Parahikma, 2018)
The research aimed to get a descriptive account of collaborative communication activities which can bridge the gaps in the view of the students and classroom condition which creates conducive atmosphere in learning English. This research applied qualitative explorative research taking the second semester students of English Literature Program at Fajar University Makassar as the purposive sample. The data were collected through Myres-Briggs online questionnaire, in depth interview, and classroom observation. The results of data analysis showed that (1) the collaborative communication activities which can bridge the students’ gaps in their perspectives should be fun and collaborative The varied activities can be applied alternately in learning interaction and adjusted with the material taught with attractive teaching media. In accordance with the gap issue, it was also found that the gap was caused by distinctive personality and personal interests, and (2) there are some classroom conditions in students’ point of view which can create conducive atmosphere physically and psychologically in learning English including the good condition of the classroom, the existence of the class attribute, and the other factors namely the lecturers, friends, motivation, and satisfaction.